Relationship between foreign direct investment and economic growth in selected transition economies - Özek, Yavuz (Statistical Economic and Social Research and, 2020)
Economies transitioning from the command economy to the free market economy experienced several important reforms throughout the transition period, these reforms have affected the sociological structures of the countries as well as the economic ones. While sociological change has an impact on the structure of the labor factor, economic transition has changed the origin and amount of capital. In this study, the effect of the transformation on the countries through the capital channel was investigated by examining the effect of foreign direct investments on transition economies in the context of economic growth. The results show that when countries are evaluated as a whole, foreign direct investments can affect the economy only in the long term. As for country-based analyzes, it is concluded that foreign direct investments are effective on economic growth in Slovakia, Slovenia and Hungary economies. © 2020, Statistical Economic and Social Research and. All rights reserved.
Keywords: Foreign Direct Investments; Panel Data; Transition Economies